On Space, On Place: A Poetic Self-Study of the Emerging Academic Identity of an International Doctoral Student - Phan, Anh Ngoc Quynh (Art/Research International)

(untitled) (University of Alberta, 2022)
Using poetic self-study, the author recounted her own lived experiences during the first year as an international doctoral student in New Zealand to explore how her academic identity emerged and (re)constructed. The article draws on theories of space and place, investigating the spatial production and social interactions of the author within spaces that, in turn, influenced her sense of being an academic. While literature has been more concerned with the questions of what activities, relations, and contexts contribute to the academic identity development of doctoral students, the author seeks to forefront the where of academic identity configuration.